TACC3 enhances glycolysis in bladder cancer cells through inducing acetylation of c-Myc - Zhirui Lin; Falian Liang; Gengde Hong; Xizhen Jiang; Qingling Zhang; Mengyao Wang (Cell Death and Disease)
Abstract The proliferation of bladder cancer (BC) cells is driven by metabolic reprogramming, marked by a glycolytic dependency to sustain uncontrolled growth. While Transforming Acidic Coiled-Coil Containing Protein 3 (TACC3) is known to promote BC progression and correlate with poor prognosis, the mechanisms underlying its upregulation and role in aerobic glycolysis remain unclear. Here, we identify E2F3 as a direct transcriptional activator of TACC3, with its amplification in BC driving elevated TACC3 expression. TACC3 overexpression enhances glycolysis, increasing glucose consumption, lactate production, and expression of glycolytic enzymes (e.g., GLUT1, HK2, PFKFB3), while its knockdown suppresses these effects. Pharmacological inhibition of glycolysis abrogates TACC3-driven tumor growth in vitro and in vivo. Mechanistically, TACC3 interacts with c-Myc, promoting its acetylation at lysine 323 (K323) by recruiting the acetyltransferase PCAF and antagonizing the deacetylase SIRT1. This acetylation stabilizes c-Myc, amplifying its transcriptional activation of glycolytic targets. Our findings establish TACC3 as a critical regulator of c-Myc-driven metabolic reprogramming in BC, highlighting its potential as a therapeutic target to disrupt glycolysis and oncogenic c-Myc signaling.